Investigation into the fatigue properties of flax fibre epoxy composites and hybrid composites based on flax and glass fibres. (1st February 2022) - Barouni, Antigoni; Lupton, Colin; Jiang, Chulin; Saifullah, Abu; Giasin, Khaled; Zhang, Zhongyi; Dhakal, Hom N.
Abstract: Natural fibre reinforced composites (NFRCs) offer a sustainable and environmentally friendly alternative to composites made from synthetic reinforcements, with their response to dynamic loading phenomena being of utmost importance for structural applications. Herein, flax fibre reinforced epoxy composites and their glass fibre reinforced hybrid counterparts were developed benefiting from synergic effects of hybridisation between flax and glass fibres with the aim of achieving optimised fatigue behaviour. In order to study the fatigue behaviour, three different types of composite laminates comprised of flax fibres only, and two hybrid flax-glass configurations were fabricated, with alternating flax/glass reinforced layers. The hybrid effects on the fatigue behaviour of all the composite laminates were investigated by using constant ratio R under a tension–tension fatigue loading. The investigated fatigue behaviour showed promising performance in the hybrid laminates, with a great effect of the hybrid configuration on the fatigue life. The hybrid laminate with alternating layers of flax and glass demonstrated the best performance under fatigue, showing a good damage accumulation indicator; about 7 times greater, as compared to the other two laminates. The statistical analysis performed indicated that the aforementioned laminate has a less probability of failure, i.e. it will fail in a greater number of fatigue cycles, as compared to the other two laminates. The influence of various parameters such as fabrication induced defects, fibre matrix interface on the fatigue life has been further characterised using imaging techniques. The findings of this study significantly contribute towards the exploitation of natural fibre reinforced composites and their hybrids to understand the damage mechanisms that take place during fatigue loadings and how the fabrication-related defects have an influence on the overall performance of those structures in load-bearing applications.